Evaluating the Immunomodulation and Hepatoprotective Activities of Hydnophytum formicarum Jack (Ant Plant) Tuber Extract in BALB/c Mouse - Putra, Wira Eka; Af’idaturrohmah, Anny; Hidayatullah, Arief; Rifa’i, Muhaimin (Iraqi Journal of Science, 2025)
Contemporary developments have indicated an escalating demand for plant-derived pharmaceutical products. Apart from their economic value, the utilization of medicinal plants is believed to pose a considerably reduced risk of adverse effects when compared to the use of synthetic drugs. One of the approaches to determine the potential of a medicinal plant against biological diseases is the quest for novel medications using natural constituents. In this present investigation, we sought to determine the immunomodulatory and hepatoprotective properties of Hydnophytum formicarum in BALB/c mice. The study used 6-week-old healthy BALB/c mice. The treatment consisted of giving different doses of H. formicarum tuber extract. To observe the immunomodulation activity, we compared the relative numbers of various immune cell subsets, such as CD4, CD8, CD4CD25, and B220 cells. Furthermore, hematoxylin and eosin staining were conducted to see how the H. formicarum extract affected liver damage. The results showed that the H. formicarum affects CD8+, CD4+, CD4+CD25+, and B220+ cells in a few spots. Importantly, the histopathological view showed that there were no significant differences between the control group and the treatment group. These results indicate that the H. fomicarum tuber extract did not harm the liver. Finally, to understand the role of H. fomicarum tuber as immunomodulator, comprehensive studies on other specific immune cells is necessary.